Using of 2-Aminothiazole Diazotised in Spectrophotometric Estimation of Cefadroxil in Dosage - Amina Daood Sulaman; Nabeel Sabeeh (African Journal of Advanced Pure and Applied Sciences, 2023)
A sensitive and simple spectrophotometric method was proposed to estimate cefadroxil in pure and capsule form. The colored product was achieved in two steps, the first step included diazotization of 2-aminothiazole with acidic NaNO2 at 0-5°C and the second step included coupling of diazotization 2-aminothiazole with cefadroxil, the orange-colored azo dye has a maximum absorption at a wavelength of 503 nm. Beer’s law was obeyed at ranging of concentrations from 1 to 12.5 µg/ml with a determination coefficient of 0.9945. A stoichiometric ratio of the reaction of diazotized 2-aminothiazole with cefadroxil was 1:1. The application for determination of cefadroxil in dosage form (capsule) via the suggested method gave accepted analytical results.